Bleeding/Bruising Symptomatology in Children with and without Bleeding Disorders - Nosek-Cenkowska, B; Cheang, M S; Pizzi, N J; Israels, E D; Gerrard, J M (Thrombosis and Haemostasis, 1991)
A questionnaire, designed to assess bleeding/bruising tendencies, was administered to 251 otherwise healthy children undergoing a tonsillectomy and/or adenoidectomy. 23 children with excessive bleeding during or after the operation, with a long bleeding time or who reported taking aspirin recently were excluded, to give a population of 228 non-bleeders. For comparative purposes, 31 patients with bleeding disorders (von Wille-brand’s disease and/or platelet function defects) were studied. A considerable proportion of “non-bleeding” children reported easy bruising (24%), had bruises at least once a week (36%) and suffered from nosebleeds (39%). The respective frequencies (67%, 68% and 69%) for children with bleeding disorders were significantly higher. Occurrence of bruises usually on more than one part of the body, frequent large bruises or hematomas were rare in “non-bleeders” (4.9%, 3.5% and 2.7% respectively), but more common in “bleeders” (38.5%, 29.6% and 21.7% respectively).